Thyrotoxic Dysphagia in an 82-Year-Old Male - Konstantinos Parperis; Ramona Dadu; Sheikh Hoq; Vivian Argento (Case Reports in Medicine)
Dysphagia is a common problem in elderly patients and a rare manifestation of Graves' disease. We report a case of an 82-year-old male who presented with a 4-week history of dysphagia and weight loss. Workup for his dysphagia with upper endoscopy, MRI brain, electromyography, acetyl-cholinesterase receptor antibodies, and voltage-gated calcium channel antibodies were negative. Modified Barium swallow test showed oropharyngeal dysphagia. Thyroid function tests that revealed hyperthyroidism and antibodies to TSH-receptor were positive. Based on the above findings, we considered Graves' disease as the most likely diagnosis. Patient was treated with methimazole and beta-blockers and subsequently his dysphagia resolved. This paper highlights the importance to clinicians of considering thyrotoxicosis as possible diagnosis in an elderly patient presenting with unexplained dysphagia.